Introductory mathematical analysis for quantitative finance - Ritelli, Daniele; Spaletta, Giulia (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"Introductory Mathematical Analysis for Quantitative Finance is a textbook designed to enable students with little knowledge of mathematical analysis to fully engage with modern quantitative finance. A basic understanding of dimensional Calculus and Linear Algebra is assumed. The exposition of the topics is as concise as possible, since the chapters are intended to represent a preliminary contact with the mathematical concepts used in Quantitative Finance. The aim is that this book can be used as a basis for an intensive one-semester course. Features: Written with applications in mind, and maintaining mathematical rigor. Suitable for undergraduate or master's level students with an Economics or Management background. Complemented with various solved examples and exercises, to support the understanding of the subject"--
Euclidean space -- Sequences and series of functions -- Multidimensional differential calculus -- Ordinary differential equations of first order : methods for explicit solutions -- Linear differential equations of second order -- Prologue to measure theory -- Lebesgue integral -- Radon-Nikodym theorem -- Multiple integrals -- Gamma and Beta functions -- Fourier transform on the real line -- Parabolic equations.
OCLC-licensed vendor bibliographic record.
Keywords: Finance -- Mathematical models; Mathematical analysis